Selling Honey and Making Money: An Instagram Marketing Strategy and Basic Photography Training for Women of Kemlagi Village, Mojokerto, East Java - Rahmawati, Aulia; Tutiasri, Ririn Puspita; Febriana, Poppy; Febriyanti, Syafrida N. (HM Publisher, 2023)
Kemlagi village is one of honey-producing village in Mojokerto, East Java, that has not been paid much attention to by the local government, both in terms of potential and marketing strategy. The involvement of housewives in the marketing sector of the Kemlagi village honey business has not been seen. This community service aims to increase women's empowerment in the social media marketing sector so that business development and community income occur. This community service has two focus activities, namely Instagram marketing training and basic photography training. The presenters of this event were a team from the Communication Science study program of the Universitas Pembangunan Nasional (UPN)